LIQUIDITY RISK MANAGEMENT PERBANKAN SYARIAH DI INDONESIA - Aulina, Nila; Yuliana, Rita; Kusufi, Muhammad Syam (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan; Vol 1 No 1 (2018): Prosiding Seminar Nasional dan Call for Papers Manajemen, Akuntansi, dan Perbankan 2018, 2018)
This study aims to provide empirical evidence on the influence of financial performance; SIZE, ROA, ROE and CAR on liquidity risk in Islamic banks as well as on conventional banks which is used as controls. This research is a quantitative research using sampling technique and equality of size in taking the data. The data is obtained by the secondary data of annual reports of sharia banks and conventional banks listed in Indonesian Banking Directory for the period 2013 until 2016. The data technique of analysis data used with multiple linear regression applys SPSS 20 software. The results show that empirical evidence which are SIZE and ROE have a negative effect on liquidity risk of sharia banks and conventional banks. These findings confirm the theory of asset liability management. ROA has no effect on liquidity risk and CAR has positive effect on liquidity risk of sharia banks and conventional banks.